The Impact of Climate Change on the Real Estate Investment in Northern Eastern Nigeria - Saad, Abdulfatai; Milala, Sani Inusa (PT.KARYA GEMAH RIPAH, 2024)
Climate change presents significant challenges to various sectors, particularly real estate investment, in regions like northeastern Nigeria, which are highly vulnerable to environmental fluctuations. This study addresses the critical need to understand how climate change impacts real estate investment decisions in states such as Borno, Yobe, Bauchi, Gombe, Taraba, and Adamawa. The primary aim of this research is to analyze the correlation between climate change impacts and real estate investment value, utilizing quantitative research methods. A structured questionnaire was distributed among real estate stakeholders, with a total sample size of 300 respondents, including 50 participants from each state in the region, employing purposive sampling for targeted insights. The analysis revealed a significant negative correlation (r = 0.65, p = 0.002) between climate change impacts and investment value, indicating that heightened environmental risks lead to decreased investor confidence and reduced property investments. Regression analysis further confirmed this trend, showing a regression coefficient of -0.50 (p = 0.001), suggesting that for each unit increase in climate change impact, real estate investment decreases by half a unit. T-test results highlighted a significant decline in investments post-climate events (t 298) = 3.45, p = 0.001), while ANOVA results demonstrated significant differences in investment levels across states (F 5, 294) = 4.20, p = 0.001). These findings collectively affirm that climate change significantly influences real estate investment decisions in northeastern Nigeria, necessitating urgent strategies for climate resilience and adaptation in the real estate sector. Stakeholders, including policymakers and investors, must recognize the importance of integrating climate considerations into their planning and decision-making processes to mitigate potential losses and foster sustainable growth in the real estate market.